Securing Potable Water Supply under Extreme Scarcity : Lessons and Perspectives from the Republic of Cyprus - Marin, Philippe; Charalambous, Bambos; Davy, Thierry (World Bank, Washington, DC, 2018)
Cyprus is one of the most water-scarce countries in the world. Starting in 1960, massive dam development was carried out under the motto “not a drop of water lost to the sea.” This supply-side policy proved its limit after two major droughts hit the island in 1997-2000 and 2008-09. This pushed for the massive development of seawater desalination and wastewater reuse through public-private partnership schemes. As of 2018, the Republic of Cyprus has successfully achieved potable water security—a remarkable achievement for one of the most water-scarce countries in the world. Despite these worthy successes, Cyprus still faces several important remaining challenges to move toward fully sustainable water management: (i) focusing on demand management, (ii) modernizing the financial and institutional framework, (iii) complying with the EU Urban Wastewater Treatment Directive, and (iv) developing a sustainable strategy for irrigated agriculture.